Hubungan lingkungan keluarga dan lingkungan sekolah berbasis agama terhadap prestasi belajar siswa - Taofik Taofik; Muhammad Nur Wangid (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine the relationship between family environment and faith based school environment and learning achievement. This research was quantitative correlational. The population was all students of fifth grade of faith based elementary school in Magelang as many as 392 students consisting of SD Muhammadiyah 1 Alternatif totaling 144 students, SDIT Ikhsanul Fikri totaling 151 students, SD Islam Al Iman totaling 40 students, SD Kristen 1 amounting to 15 students and SD Pantekosta totaling 38 students.The sample was 198 students, selected by purposive random proportional sampling technique. The study data were collected with family environment questionnaire, faith based school environment questionnaire, and documentation of learning achievement. Validity test was done by expert judgment and with the help of SPSS 20.0 for Windows. Reliability testing used Cronbach's alpha technique. The results showed that: (1) there was a positive relationship between the family environment and learning achievement, (2) there was a positive relationship between faith based school environment and learning achievement, the (3) there was a positive relationship between family environment and faith based school environment with learning achievement. The existence of a positive contribution value means that parents in the family environment and teachers in a faith based school environment always provide support for the child's learning process.